HUBUNGAN ANTARA BODY IMAGE DENGAN PENERIMAAN DIRI PADA MAHASISWA ACEH DI YOGYAKARTA - Ridha, Muhammad (Universitas Ahmad Dahlan, 2013)
AbstractThis research aims to know the relationship between Body Image and Self- acceptance of student. The subject of this research is Aceh student who lives in Dormitory at Yogyakarta. Data collection tools used in this research is scale of Body Image and Self-acceptance. Data analysis method using correlation of Pearson Product Moment The result showed that significant that there is a positive relationship between body image and self-acceptance at a student dormitory located in Yogyakarta. The relationship indicated by a correlation coefficient ( r ) = 0,318, ( = 0,013 p ). The contribution of effective body image by the reception is worth 10,11 %. Conclusion in this research is a significant positive relationship between a body image and self-acceptance of Aceh students who lives in Jogjakarta. These results informed that higher body image makes high self-acceptance. Then, the lower body image makes low self-acceptance.Keywords: body image, self-acceptance